The association between three major physiological stress systems and oxidative DNA and lipid damage. (June 2017) - Black, Catherine N.; Bot, Mariska; Révész, Dóra; Scheffer, Peter G.; Penninx, Brenda
Highlights: This large-scale cohort examined associations between physiological stress and oxidative damage. Oxidative DNA damage is associated with inflammatory, HPA-axis and ANS markers. Oxidative lipid damage is associated with inflammatory and ANS markers. This study found a dose-response relationship between physiological stress and oxidative damage. Abstract: Background: Increased activity of the three major physiological stress systems (immune-inflammatory system, hypothalamic-pituitary-adrenal-axis [HPA-axis], and autonomic nervous system [ANS]) is part of the pathophysiology of various somatic and psychiatric diseases. Oxidative damage is a key mechanism in both ageing and disease. Elucidating the relationship between these stress systems and oxidative damage would contribute to the understanding of the role of physiological stress in disease. This study therefore investigates associations between various measures of physiological stress and oxidative DNA (8-hydroxy-2′-deoxyguanosine, 8-OHdG) and lipid (F2-isoprostanes) damage. Methods: Plasma 8-OHdG and F2-isoprostanes were measured using LC–MS/MS in 2858 subjects (aged 18–65). Plasma inflammation markers, salivary cortisol and ANS markers (three for each stress system) were determined. Linear regression analyses were adjusted for sociodemographics, sampling factors and medication. Results: 8-OHdG was positively associated with all inflammation markers (β = 0.047–0.050, p < 0.01), evening cortisol (β = 0.073, p < 0.001), and unexpectedly with low respiratory sinus arrhythmia (RSA) reflecting low ANS stress (β = 0.073, p < 0.001). F2-isoprostanes were associated with higher C-reactive protein (β = 0.072, p < 0.001), high ANS stress reflected in heart rate (β = 0.064, p < 0.001) and RSA (β = −0.076, p = 0.001), but not with cortisol. Analyses investigating the cumulative impact of the stress systems demonstrated that the number of systems with ≥1 marker in the high risk quartile showed a positive linear trend with both 8-OHdG (p = 0.030) and F2-isoprostanes (p = 0.009). Conclusion: This large-scale study showed that markers of inflammation, the HPA-axis and ANS are associated with oxidative DNA damage. Oxidative lipid damage is associated with inflammation and the ANS. Increased physiological stress across systems is associated with increasing oxidative damage in a dose-response fashion.